Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0959683616675939
|View full text |Cite
|
Sign up to set email alerts
|

All age–depth models are wrong, but are getting better

Abstract: The construction of accurate age–depth relationships and a realistic assessment of their uncertainties is one of the fundamental prerequisites for comparing and correlating late Quaternary stratigraphical proxy records. Four widely used age–depth modelling routines – CLAM, OxCal, Bacon and Bchron – were tested using radiocarbon dates simulated from varved sediment stratigraphies. All methods produce mean age–depth models that are close to the true varve age, but the uncertainty estimation differs considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 29 publications
1
87
1
Order By: Relevance
“…They also found that the impact of different values for thickness was dependent on acc.shape, the accumulation shape prior. As Blaauw and Christen (2011) did not explicitly make any recommendations for how to choose an appropriate value for thickness, Trachsel and Telford (2017) suggested that the length be shorter than the mean distance between dated intervals and to choose a value that allowed for faster model convergence.…”
Section: S5 Parameters and Priors Used For Bacon Age-depth Modelmentioning
confidence: 99%
“…They also found that the impact of different values for thickness was dependent on acc.shape, the accumulation shape prior. As Blaauw and Christen (2011) did not explicitly make any recommendations for how to choose an appropriate value for thickness, Trachsel and Telford (2017) suggested that the length be shorter than the mean distance between dated intervals and to choose a value that allowed for faster model convergence.…”
Section: S5 Parameters and Priors Used For Bacon Age-depth Modelmentioning
confidence: 99%
“…Despite the benefits of low-resolution archives, these records often contain relatively large errors associated with radiometric dating techniques (Anchukaitis and Tierney, 2012;Moberg et al, 2005) and uncertainty associated with using age-depth models to predict ages of undated layers (Trachsel and Telford, 2017;Telford et al, 2004). Age ambiguity leads to difficulty in cross-correlating records.…”
Section: Caveats On Resolving Changes From Low-resolution Sedimentarymentioning
confidence: 99%
“…Although classical age-depth modeling may underestimate the uncertainties inherent to radiocarbon dating (Blaauw et al 2018), we decided to continue using this approach because gaining realistic influx values (charcoal and dung fungal spores) is crucial for this study. Indeed, the Bayesian routines currently available provide unrealistic deposition time estimates because they are based on piecewise linear models that create large jumps around the radiocarbon-dated levels (Trachsel and Telford 2017). However, we considered the 95% confidence intervals of the estimated ages obtained with Bacon 2.3.6 (Brezoso, default settings; Viñuelas, thick = 2, acc.mean = 50, acc.shape = 1.3), a Bayesian approach to age-depth modeling that takes into account chronological ordering and sedimentation by sampling from gamma and beta distributions (Blaauw and Christen 2011), instead of those provided by clam.…”
Section: Coring Radiocarbon Dating and Age-depth Modelingmentioning
confidence: 99%